An Age-based Analysis of the Perceptions of Ageing and Successful Ageing in Malaysia - Cheng, Ming Yu; Low, Sew Kim; Pheh, Kai-Shuen (UI Scholars Hub, 2021)
As ageism could have detrimental effects in the ageing society, it is important to know how people of different age groups perceive ageing and successive ageing. This study collected data from 648 respondents aged between 18 to 80 years old for an age-based analysis of the perceptions of ageing and successful ageing. Self- administered questionnaires were used. Correlation analysis was conducted to examine the relationship between perception of successful ageing and factors associated with psychological well-being. Our results revealed that generally, being healthy, happy and physically active are considered as important aspects of successful ageing. Younger people considered life satisfaction as an important aspect of developing positive perceptions of ageing, while physical ability and life satisfaction are important factors for middle-aged adults. For older people, quality of life, good economic and health status are essential to developing successful ageing. Regardless of age, health is perceived as the most fundamental part of life. The findings offer valuable insights for the formulation of strategies to address the social and economic challenges of an ageing society.